Handbook of Financial Risk Management: Simulations and Case Studies (Journal of Entrepreneurship, Management and Industry (JEMI), 2022)
The United States subprime mortgage crisis was a multinational financial crisis that occurred between 2007 and 2010 that contributed to the global financial crisis. It demonstrated that widely adopted risk management instruments, such as Credit Default Swaps (CDS), Collateralized Debt Obligation ( CDO), and other CDO’s, can be amplifiers instead of mitigators of risk. Headlines such as “Did a mathematical formula really blow up Wall Street...?” and “Living on the edge” became the norm. What really happened in 2008...? The answer and verdict are yet to be found.